Successful approaches to integrated water resources management : a mini review - Zuriyati Yusof; Noor Aida Saad (Penerbit Universiti Kebangsaan Malaysia, 2022)
River basins must be handled in a comprehensive and integrated way. To achieve that, Integrated River Basin Management (IRBM) is a strong concept that will increasingly win discussions on natural resource management. IRBM focuses on the integration and coordination of policies, programs and practices. It focuses on problems relating to water and rivers. It advocates for improved skills and increased financial, legislative, management and political will. Many developed countries have expanded strongly functional and stable institutions for IRBM. These structural models have developed through the years, and are being gradually imposed and encouraged by policymakers and funders in developing countries. The main goal of this research is to identify and combine the main goals, concepts, effective practice examples and lesson learned of Integrated River Basin Management that emerged from the best practices management of River Thames in United Kingdom, European Unions’ Water Framework Directive, IWRM Canada and Malaysia. This research’s methodological approach compares the implementation structure of IWRM in four countries. The countries were chosen based on their numerous efforts in the field of water resource management. This is a practical water management framework focused on a holistic view of society’s goals integrated into good governance and sustainable development concepts. It also explains the advantages of expanding the idea behind IWRM core concepts.